Breaking the cycle: a review of the impacts of maternal PTSD, adverse pregnancy outcomes, and health disparities among Black women - Tiffany R. Williams; Christina Scifres; David M. Haas (Maternal Health, Neonatology and Perinatology, 2026)
Abstract Posttraumatic stress disorder (PTSD) is an underrecognized contributor to maternal morbidity, infant health complications, and rising healthcare costs. This narrative review synthesizes interdisciplinary evidence on the pathways linking structural inequities, trauma exposure, and maternal PTSD to adverse maternal and infant outcomes, with particular attention to the disproportionate burden experienced by Black women. Structural racism and systemic inequities increase exposure to chronic stress and trauma, which in turn elevate risk for PTSD during the perinatal period. Maternal PTSD functions as a central mechanism linking upstream inequities to downstream health outcomes. Through dysregulation of stress-responsive biological systems and associated behavioral pathways, PTSD increases the risk of adverse maternal outcomes, including hypertensive disorders, preterm birth, and severe maternal morbidity, as well as infant outcomes such as low birth weight, neurodevelopmental and emotional regulation difficulties, and impaired mother–infant attachment. These relationships are bidirectional, with adverse pregnancy and birth experiences further contributing to the onset or exacerbation of PTSD symptoms, reinforcing a cycle of psychological and physiological vulnerability. These interconnected maternal and infant outcomes contribute to substantial healthcare utilization and economic burden at individual and societal levels. The cumulative impact of perinatal mental health conditions exceeds $14 billion annually in the United States, driven in part by adverse birth outcomes and downstream developmental consequences. Addressing this cycle requires trauma-informed, integrated care models that incorporate universal screening, improve access to evidence-based treatment, and address structural barriers to care. Developing scalable, culturally responsive interventions may help reduce disparities, improve maternal and infant outcomes, and mitigate long-term societal costs.